Design and Implementation of Arduino-Based NRF Remote Control Steering System for Hand Tractors to Enhance Agricultural Efficiency - Rukmana, Ade; Firmansyah, Wasep; Oktafiani, Folin; Artemysia, Khaulyca Arva; Nurpadilah, Sifa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Hand tractors are crucial for small-scale farming in Indonesia, but prolonged manual operation leads to operator fatigue, reduced productivity, and safety risks. This study develops a wireless steering control system for a hand tractor using an Arduino microcontroller and NRF24L01 transceiver. The system features a handheld transmitter with joystick input and a tractor-mounted receiver that controls the throttle via a servo motor and steering/clutch mechanisms through solenoids. The design process included system architecture, hardware and power circuit development, software programming, prototype assembly, and testing. Results show that the system operates optimally within 1–2 meters and remains functional up to 8 meters, though with communication degradation (increased delay, packet loss, and reduced actuator accuracy). Key constraints identified include unstable power supply, NRF24L01 limitations, and inadequate solenoid drivers. Recommendations for improvement include using NRF24L01+ PA/LNA modules, separating power rails, and adopting MOSFET-based drivers to enhance reliability and safety.